(untitled) (Historia, 2021)
Afrikaans In die negentiende eeu het vier Portugese reisigers die Transvaal besoek, naamlik Joaquim de Santa Rita Montanha (1806-1870) in 1855-1856, Diocleciano Fernandes das Neves (1829-1883) in 1860-1861, Fernando Augusto da Costa Leal (1846-1910) in 1869-1870 en Alexandre Alberto da Rocha de Serpa Pinto (1846-1900) in 1879. Hulle het almal reisjoernale bygehou, wat later in Portugees, maar ook in vertaalde vorm gepubliseer is. Dié joernale is van belang vir natuurkundiges, maar bowenal vir historici, kultuurhistorici, etnoloë en antropoloë omdat die reisigers onder meer oor die verspreiding, voorkoms, karakter, lewenswyse en -vorme van die inwoners van die Transvaal, waaronder die Boere en die verskillende inheemse groepe waarmee hulle onderskeidelik in aanraking gekom het, gerapporteer het. Hoewel die reisjoernale van Montanha en Das Neves in die verlede wel deur navorsers geraadpleeg is, behoort die inhoud van die joernale van Da Costa Leal en Serpa Pinto in die toekoms behoorlik ontgin te word. English Portuguese Travellers in the Transvaal in the Nineteenth Century In the nineteenth century four Portuguese travellers visited the Transvaal, namely Joaquim de Santa Rita Montanha (1806-1870) in 1855-1856, Diocleciano Fernandes das Neves (1829-1883) in 1860-1861, Fernando Augusto da Costa Leal (1846-1910) in 1869-1870, and Alexandre Alberto da Rocha de Serpa Pinto (1846-1900) in 1879. They all kept travel-journals which were later published in Portuguese, as well as translated into and published in other languages. The journals are of interest to natural scientists, but especially to historians, cultural historians, ethnologists and anthropologists. This is because the travellers reported, among other matters, on the distribution, appearance, lifestyle and customs of the inhabitants of the Transvaal, including the Boers and various indigenous groups with whom they came into contact. Although researchers have in the past consulted the journals of Montanha and Das Neves, the contents of the journals of Da Costa Leal and Serpa Pinto deserve to be explored more thoroughly in future.